Prevalence of symptoms of depression, anxiety, insomnia, posttraumatic stress disorder, and psychological distress among populations affected by the COVID-19 pandemic: A systematic review and meta-analysis. (January 2021) - Cénat, Jude Mary; Blais-Rochette, Camille; Kokou-Kpolou, Cyrille Kossigan; Noorishad, Pari-Gole; Mukunzi, Joana N.; McIntee, Sara-Emilie; Dalexis, Rose Darly; Goulet, Marc-André; Labelle, Patrick R.
Highlights: Infectious disease outbreaks are associated with mental health symptoms and disorders. Pooled prevalence of depression, anxiety, insomnia, PTSD, and psychological distress were 15.97%, 15.15%, 23, 87%, 21.94%, and 13.29%, respectively. No significant differences were observed for gender, geographical regions, and healthcare workers (except for insomnia, which was more prevalent among healthcare workers). This study provides findings that will guide research and the development of better mental health programs during and after the pandemic. Abstract: Objective: We conducted a systematic review and meta-analysis to estimate the pooled prevalence of depression, anxiety, insomnia, PTSD, and Psychological distress (PD) related to COVID-19 among affected populations. Methods: We searched articles in Medline, Embase, APA PsycInfo, CINAHL, Scopus, and Web of Science. Random-effects meta-analyses on the proportions of individuals with symptoms of depression, anxiety, insomnia, PTSD, and PD were generated and between-group differences for gender, healthcare workers (HCWs), and regions where studies were conducted. Results: A total of 2189 articles were screened, 136 full-text articles were assessed for eligibility. Fifty-five peer-reviewed studies met inclusion criteria for the meta-analysis ( N =189, 159). The prevalence of depression ( k =46) was 15.97% (95%CI, 13.24-19.13). The prevalence of anxiety ( k =54) was 15.15% (95%CI, 12.29-18.54). The prevalence of insomnia ( k =14) was 23.87% (95%CI, 15.74-34.48). The prevalence of PTSD ( k =13) was 21.94% (95%CI, 9.37-43.31). Finally, the prevalence of psychological distress ( k =19) was 13.29% (95%CI, 8.80-19.57). Between-group differences were only found in HCWs ( z =2.69, p < 0.05) who had a higher prevalence of insomnia than others. Conclusions: Findings suggest that the short-term mental health consequences of COVID-19 are equally high across affected countries, and across gender. However, reports of insomnia are significantly higher among HCWs than the general population.